Accelerated wound healing in a diabetic rat model using decellularized dermal matrix and human umbilical cord perivascular cells. (November 2016) - Milan, P. Brouki; Lotfibakhshaiesh, N.; Joghataie, M.T.; Ai, J.; Pazouki, A.; Kaplan, D.L.; Kargozar, S.; Amini, N.; Hamblin, M.R.; Mozafari, M.; Samadikuchaksaraei, A.
Graphical abstract: Abstract: There is an unmet clinical need for novel wound healing strategies to treat full thickness skin defects, especially in diabetic patients. We hypothesized that a scaffold could perform dual roles of a biomechanical support and a favorable biochemical environment for stem cells. Human umbilical cord perivascular cells (HUCPVCs) have been recently reported as a type of mesenchymal stem cell that can accelerate early wound healing in skin defects. However, there are only a limited number of studies that have incorporated these cells into natural scaffolds for dermal tissue engineering. The aim of the present study was to promote angiogenesis and accelerate wound healing by using HUCPVCs and decellularized dermal matrix (DDM) in a rat model of diabetic wounds. The DDM scaffolds were prepared from harvested human skin samples and histological, ultrastructural, molecular and mechanical assessments were carried out. In comparison with the control (without any treatment) and DDM alone group, full thickness excisional wounds treated with HUCPVCs-loaded DDM scaffolds demonstrated an accelerated wound closure rate, faster re-epithelization, more granulation tissue formation and decreased collagen deposition. Furthermore, immunofluorescence analysis showed that the VEGFR-2 expression and vascular density in the HUCPVCs-loaded DDM scaffold treated group were also significantly higher than the other groups at 7 days post implantation. Since the rates of angiogenesis, re-epithelization and formation of granulation tissue are directly correlated with full thickness wound healing in patients, the proposed HUCPVCs-loaded DDM scaffolds may fulfil a role neglected by current treatment strategies. This pre-clinical proof-of-concept study warrants further clinical evaluation. Statement of Significance: The aim of the present study was to design a novel tissue-engineered system to promote angiogenesis, re-epithelization and granulation of skin tissue using human umbilical cord perivascular stem cells and decellularized dermal matrix natural scaffolds in rat diabetic wound models. The authors of this research article have been working on stem cells and tissue engineering scaffolds for years. According to our knowledge, there is a lack of an efficient system for the treatment of skin defects using tissue engineering strategy. Since the rates of angiogenesis, re-epithelization and granulation tissue are directly correlated with full thickness wound healing, the proposed HUCPVCs-loaded DDM scaffolds perfectly fills the niche neglected by current treatment strategies. This pre-clinical study demonstrates the proof-of-concept that necessitates clinical evaluations.